Use of phytotherapy and other vegetable and mineral components in the manufacture of natural dental products: Literature review (Research, Society and Development, 2021)
Phytotherapics and other plant and mineral components are defined as a way of using natural products for the treatment of diseases, enabling various benefits to users, provided they are used correctly. The purpose of herbal medicines is to cure, prevent or minimize the symptoms of diseases, in addition to being more accessible to the population than synthetic medicines. Thus, natural products, because they have antifungal, antimicrobial and antineoplastic activities, are considered a great alternative in oral treatments, assisting dental surgeons and patients in the control of biofilm. In this context, the objective of this work is to clarify the benefits and effectiveness of some natural dental products and their contraindications, in addition to explaining the advantages and disadvantages of using such products. The methodology developed in the present work was to carry out a narrative review of the literature, being researched in scientific databases, such as: Scielo, Bvsalud, Redalyc and Sciencedirect. The use of herbal medicines demonstrates as a result a series of advantages and disadvantages which fluctuate depending on the way they were used, they present several benefits for both patients and public health services, which facilitates their adherence to these services. It is concluded that the correct use of herbal medicines is a great alternative therapy in the treatment of oral diseases and provides a series of benefits for oral health, since natural products are more accessible because they have lower prices than synthetic products in addition less toxicity.